Francisco Javier Clavijero, actor and witness of History: writing as an instrument of subversion against the King and the Papacy - Escalante Adaniya, Marie Elise (2024)
The current study analyses two little-studied works by the Mexican Jesuit historian Francisco Javier Clavijero: a testimony and a letter that discuss the causes of the expulsion of the Jesuits from Mexico and narrate the hardships of European exile. These two speeches have a subversive character, because they question the legitimacy of the king and the pope, and establish an implicit alliance with the people who mutinied against the Jesuit exile. On the other hand, the historian’s deep resentment against the French Enlightenment, which was, according to him, the main driving force behind the expulsion from Europe and America, is revealed. Clavijero uses his testimony and his letter to confront the exceptional power of the king, to judge and condemn the pope, and to argue that it will be posterity that will do justice to the Jesuit religious order. Writing becomes a means of questioning power, vindicating his order, and keeping a memory of these fateful events.